Importance to establish and deploy technical management processes to support organizations : A case study - Shamsuzzoha, Ahm; Syrjälä, Anniina (SAGE Publications, 2024)
Due to today’s intense competition and rapid changes in the market, organizations must concentrate on their process management to improve their effectiveness to be able to respond quickly. Studies have shown that organizations are not necessarily even aware of the current primary function of technical management (TM) because their internal procedures are not currently modeled. This results in a lack of efficiency in terms of how businesses operate in organizations. This study aims to create internal procedure manuals for the technical support function of a case company and considers how to pinpoint areas for process improvement. Since TM is a part of the case company internally, it has not been able to update its internal procedure charts to reflect this, so cannot show its current roles in the surrounding organization. The methodology of this study is separated into two stages: modeling swim lane diagrams describing the existing state (as-is) of TM processes and then conducting semi-structured interviews with key stakeholders to ascertain their expectations and suggestions for change. Thematic analysis of the interview data and performing a comparison with the current procedure charts are used to determine whether or not TM’s procedures can be strengthened to better assist the surrounding organization. The study concludes that further actions are needed to clarify the role of TM in ways other than in the sub-process task level in the procedure charts of the case company. In addition, TM could conduct further analysis to optimize the case company’s business processes to achieve maximum benefit in the future.
Keywords: Business process; process development; swim lane diagram; business process management; process modeling; as-is analysis; procedure chart; fi=Tuotantotalous|en=Industrial Management|